2012
DOI: 10.1007/s10562-012-0794-4
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Catalytic Activity of Carbon Black during Methane Decomposition: Active Site Estimations from Surface Structural Characteristics

Abstract: The variation in the catalytic activity of carbon black (CB) during methane decomposition was investigated by considering the number of active sites of CB. We demonstrated that the activity variation could be well estimated by assuming the edge length of graphitic sheets evolving from the CB surface. The results suggested that the activity variation originated from surface structural changes due to carbon deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The conversion of methane with different types of carbon materials is expected to be similar in the late stages of the processes due to the formation of carbon deposits (coke) on the surface, which hinder the longevity of the carbon catalyst for hydrogen production . To the best of our knowledge, most of the current understanding of the effect of surface structure and doping on the CMD process is based on extrapolation of specific reaction steps’ findings ,, to the overall process and studies investigating the effect of heteroatomic doping toward the nonoxidative hydrogen production from methane on carbonaceous catalysts are lacking. , Therefore, it is mandatory that a thorough atomistic investigation of the CMD process, based on the carbonaceous catalyst structure modification, is performed in order to give insights about the main reaction mechanism, aiming at predicting intermediates’ and byproducts’ production at desired conditions, elucidating the main hydrogen formation channels and to guide the catalyst engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The conversion of methane with different types of carbon materials is expected to be similar in the late stages of the processes due to the formation of carbon deposits (coke) on the surface, which hinder the longevity of the carbon catalyst for hydrogen production . To the best of our knowledge, most of the current understanding of the effect of surface structure and doping on the CMD process is based on extrapolation of specific reaction steps’ findings ,, to the overall process and studies investigating the effect of heteroatomic doping toward the nonoxidative hydrogen production from methane on carbonaceous catalysts are lacking. , Therefore, it is mandatory that a thorough atomistic investigation of the CMD process, based on the carbonaceous catalyst structure modification, is performed in order to give insights about the main reaction mechanism, aiming at predicting intermediates’ and byproducts’ production at desired conditions, elucidating the main hydrogen formation channels and to guide the catalyst engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The CB used herein has a high specific surface of 68 m 2 ·g ¹1 , which is almost equal to that of CB used in prior reports. 17)19) The rate of H 2 production from CH 4 by using CB as a catalyst was measured by using a gas reaction system. A schematic of the gas reaction system is presented in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The flow rate of CH 4 per sectional area of the reactor was 0.0051 sccm·mm ¹2 , which is about one hundredth of the flow rate per sectional area used in prior reports. 15), 17) The reactor was then heated to 5001100°C, and the reaction between CH 4 and CBs was started. The reacted gas was analyzed to identify the generated gases and evaluate the temperature-dependence of the gas generated via GC.…”
Section: Methodsmentioning
confidence: 99%
“…Four separate studies have shown low-resolution TEM of deposited carbon on carbon blacks [47,[66][67][68]. Results diverge, showing either uniformity of deposition or non-uniformity, though results in both cases are difficult to gauge given varied reactor bed configurations.…”
Section: Electron Microscopy In Tcdmentioning
confidence: 99%